Colour Changes of Weathered Wood Surfaces Before and After Treatment with Iron (II) Sulphate - Boštjan Lesar; Miha Humar; Florjan Osvald (Drvna Industrija, 2024)
Outdoor wood is exposed to various factors that can be described as weathering and cause the wood to grey. The ageing processes can vary greatly depending on the exposure. Parts of wood that are not exposed to external factors, e.g. under the overhanging, are less exposed, and the weathering process is therefore slower. This can be accelerated by solutions based on iron ions. In this way, the wood greys quickly and evenly. However, after iron treatment, the colour also depends on the previous exposure of wood to weathering. In our study, the colour change was observed as a function of weathering time. Before treatment, the samples were exposed to outdoor weathering for different periods of time and then treated with a 5 % solution of pure iron (II) sulphate and commercial iron (II) sulphate. It was determined that the pre-weathering time affected the final colour change, as the samples exposed for five weeks before treatment have comparable colour to naturally weathered wood. At the beginning of exposure, iron (II) sulphate limits mould growth, but after two months, staining fungi develop on the treated samples as well. The growth of blue stain fungi on the treated samples did not significantly affect the colour and visual appearance of the wood treated with iron-based solutions.